If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57.2 + a * x + b * yandx + y = 1 Multiply a * x 57.2 + ax + b * yandx + y = 1 Multiply b * adnxy 57.2 + ax + abdnxy + y = 1 Reorder the terms: 57.2 + abdnxy + ax + y = 1 Solving 57.2 + abdnxy + ax + y = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-57.2' to each side of the equation. 57.2 + abdnxy + ax + -57.2 + y = 1 + -57.2 Reorder the terms: 57.2 + -57.2 + abdnxy + ax + y = 1 + -57.2 Combine like terms: 57.2 + -57.2 = 0.0 0.0 + abdnxy + ax + y = 1 + -57.2 abdnxy + ax + y = 1 + -57.2 Combine like terms: 1 + -57.2 = -56.2 abdnxy + ax + y = -56.2 Add '-1y' to each side of the equation. abdnxy + ax + y + -1y = -56.2 + -1y Combine like terms: y + -1y = 0 abdnxy + ax + 0 = -56.2 + -1y abdnxy + ax = -56.2 + -1y Reorder the terms: 56.2 + abdnxy + ax + y = -56.2 + -1y + 56.2 + y Reorder the terms: 56.2 + abdnxy + ax + y = -56.2 + 56.2 + -1y + y Combine like terms: -56.2 + 56.2 = 0.0 56.2 + abdnxy + ax + y = 0.0 + -1y + y 56.2 + abdnxy + ax + y = -1y + y Combine like terms: -1y + y = 0 56.2 + abdnxy + ax + y = 0 The solution to this equation could not be determined.
| 2.5x+20=3x-4 | | X-11=-6 | | -2x+18=3x+33 | | 45b=25 | | (7y-8)-(5+6y)=9 | | 7=35n | | 95+13x+5=3x+10 | | -5.2=3w-3.4w | | 300x^2-240x+32=0 | | 5-8.5x=6.7-7.5x | | 4m-15=33 | | 3z+3=4z-14 | | y=2x^2-5x-42 | | 2w(w+2w)=18 | | y=2x^2-5x-43 | | -5x(x+y)=20+3x | | 5-7=d | | 4(3x-2)+5x=6(2x+8)-12 | | 3*(x-5)=15 | | y=144x^3-25x | | 4(n+5)+(n+7)=54 | | 49=t+16 | | (3z-2)(3z+8)=(z-4)(z+4) | | 2y+6+10=18-2y | | -11+r=37 | | (2COSx+1)sinx=0 | | (3z-2)(3z+8)= | | 8+x=13+12x | | 7(a+5)=84 | | 11x^2-31x-54=0 | | 2m+r=28 | | 36x^2=180 |